“La gestión administrativa y su incidencia en la producción y productividad de las pequeñas fincas agrícolas de banano del cantón La Mana, provincia de Cotopaxi. Año 2020”. - Arellano Mendez, Liliana Lorena (2021)
The present investigation titled “Administrative management and its impact on the production and productivity of small banana farms in La Maná canton, Cotopaxi province, year 2020” is based on identifying the elements of administrative management and its impact on the production and productivity of small agricultural banana farms in La Maná canton. For the collection of primary source information, it was necessary to use a methodology based on the application of the deductive and analytical method through the use of the survey technique and with the designed questionnaire that were applied to the owners and employees of the agricultural production units. It was possible to obtain the necessary information to respond to the objectives in the research process. The collected information is presented in tables and statistical graphs and allowed the analysis of the obtained results and the design of a proposal to be applied in each of the farms so allowing better production processes and thereby improving the levels of production and productivity of these units of production. Field research was applied to 20 banana farms that have from ten to twelve hectares of bananas in production that are distributed in six productive sectors of the study area such as: Tres Coronas, Salento, Los Laureles, La Juan Cobo, San Antonio de Manguila and Bella Jungla. The results of the investigation allow determining that the farms in San Antonio de Manguila have an average production cost of 84,470.37 dollars with an average annual production of 19,800 boxes, giving a total unit cost of 4.27 dollars / box. Regarding financial profitability, the accounting information allows to deduce that the banana farms in San Antonio de Manguila present a better level of profitability with a net profit of 29,348.44 dollars and followed by the farms in the Tres Coronas with 27,554.30 dollars of net profit. Regarding the reasons for return on income and productivity, it can be interpreted that the gross profit margin of San Antonio de Manguila obtained 48.5% of benefits, it obtained higher gross profit and better net sales, including the farms that present a better operating profit margin compared to the other farms. It is also deduced that there is an average production of 21,826 boxes / year which generates a total production of 435,656 boxes / year in the 20 farms under study, generating a total income of 2,788,198.40. dollars. The obtained information allows to conclude that the small farms in La Maná canton have an acceptable profitability and improve the management processes in production, so improving the production and profitability indicators.